Penerapan Structural Equation Modelling-Partial Least Square pada Faktor-Faktor yang Memengaruhi Keputusan Pembelian Usaha MyCake.Ofc - Siti Nurmardia Abdussamad; Amanda Adityaningrum; Muhammad Rezky Friesta Payu; Syafri Yandi Kudo; Desya Neydi Putri Pakaya; Qamarani Zatil Isma Darise (Research in the Mathematical and Natural Sciences, 2026)
This study aims to analyze the influence of product, price, and promotion on purchasing decisions at MyCake.Ofc using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. Data were collected through questionnaires distributed to 100 respondents in Gorontalo City, selected using purposive sampling techniques. The analysis results show that price has a significant influence on purchasing decisions, while the product and promotion variables do not have a significant effect. The research model has an R-square value of 97.6%, indicating that the product, price, and promotion variables explain 97.6% of the variation in purchasing decisions.. This study highlights the importance of competitive pricing strategies to enhance consumer appeal and purchasing decisions in the food business sector, particularly at MyCake.Ofc.